2005
DOI: 10.1111/j.1600-0633.2005.00079.x
|View full text |Cite
|
Sign up to set email alerts
|

The smolt run and postsmolt survival of Atlantic salmon, Salmo salar L., in relation to early summer water temperatures in the northern Baltic Sea

Abstract: The smolt run and postsmolt survival of Atlantic salmon, Salmo salar L., in relation to early summer water temperatures in the northern Baltic Sea Un resumen en españ ol se incluye detrás del texto principal de este artículo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(75 citation statements)
references
References 28 publications
2
73
0
Order By: Relevance
“…Timing of seaward migration is modulated by temperature and fl ow, and perhaps the lunar cycle (Wedemeyer et al 1980 ;McCormick et al 1998 ;Jutila et al 2005 ;Thorstad et al 2011 [Chapter 1 ]; Fig. 16.5 ).…”
Section: Smolt M Igrationmentioning
confidence: 99%
See 3 more Smart Citations
“…Timing of seaward migration is modulated by temperature and fl ow, and perhaps the lunar cycle (Wedemeyer et al 1980 ;McCormick et al 1998 ;Jutila et al 2005 ;Thorstad et al 2011 [Chapter 1 ]; Fig. 16.5 ).…”
Section: Smolt M Igrationmentioning
confidence: 99%
“…Higher temperatures may advance the smolt run timing but photoperiod will presumably also restrict advancement. Jutila et al (2005) reported the main smolt run in a northern Baltic river to be abbreviated in years when migration was delayed by freshwater conditions, and they also showed that early summer SST which is either too low ( < 9 ° C) or too high ( > 12 ° C) at entry was detrimental to post -smolt survival. Because very early post -smolt mortality is typically high (Klemetsen et al 2003 ), the implications are that timing of seawater entry has consequences for metabolic costs, physiological stress, prey availability and the likelihood of predation ).…”
Section: Smolt M Igrationmentioning
confidence: 99%
See 2 more Smart Citations
“…Water temperature partly regulates fish migrations by determining the direction of migration or stimulating the initiation of migratory activity and combines with other stimuli, such as discharge and photoperiod (McFarland, 1971;Northcote, 1984Northcote, , 1998Crisp 1996). The main factor initiating downstream migration of smolt (Jutila et al, 2005) is a rise in water temperature to over 10°C. This did not happen in 2003 when the temperature ranged from 4.3-12.3°C, whereas in 2004 temperatures were higher (9.6-16.1°C).…”
Section: Discussionmentioning
confidence: 98%